Improving the Eleventh Grade Students’ Reading Comprehension of Narrative Text Through Two Stay Two Stray Technique - Yocka Meiliana Nadia Utama; Wawan Prasetyo (STKIP PGRI Trenggalek, 2022)
English is one of compulsory subject which is taught in Indonesian school, and reading is one of language skills that is almost dominant in teaching learning process. This research was conducted to improve the students’ reading comprehension through two stay two stray technique. The research design which used is Collaborative Classroom Action Research. This research was done in to two cycles. In the post-test first cycle there were 32% students who passed the test, and in the post-test second cycle there were 84% students who passed the test. From the data above it can be concluded that the implementation of Two Stay Two Stray technique can improve students’ reading comprehension of narrative text